Community case study: Our Wave, an online platform to facilitate survivor disclosure of sexual assault and trauma recovery - Sinko, Laura; Naidenko, Olga V.; Michaelsen, Brendan; Marzke, Cassandra; Hart, Madeline; Tweedie, Brooke; Linton, Kyle (Frontiers in Public Health, 2024)
This community case study introduces Our Wave, an online platform that provides a safe, anonymous space for survivors of sexual harm to share their stories, reflect on their healing journeys, and connect with others. Designed to empower survivors, the platform allows users to post anonymous stories or visual media, ask questions, and send messages of hope, all while prioritizing privacy and security. It also aims to create a broader impact by analyzing shared narratives to detect patterns, identify best practices for healing, and inform global approaches to SV recovery. With over 100,000 members and over 1,200 stories and forms of media shared, the platform has become a valuable resource for survivors. Using mixed-methods analysis of platform usage data and anonymous user feedback surveys (n = 288), we examined patterns of engagement and impact. Analysis revealed that 57% of story submissions included “Messages of Healing” and 52% included “Messages of Hope,” with survey responses indicating that anonymity and peer support were crucial factors in facilitating disclosure. Research shows that the social and emotional dynamics of SV disclosure, as well as the responses from others, play a crucial role in a survivor’s healing. By focusing on confidentiality, trauma-informed support, and community-building, Our Wave offers a safe space for survivors to heal, connect, and access resources to support their journey toward recovery.